2019
DOI: 10.1029/2019gc008518
|View full text |Cite
|
Sign up to set email alerts
|

Localized Anisotropic Domains Beneath Eastern North America

Abstract: Seismic anisotropy beneath eastern North America likely reflects both the remnant lithospheric fabrics and the present‐day deformation of the asthenosphere. We report new observations of splitting in core‐refracted shear phases observed over 3–5 years at 33 sites in New Jersey, New York, and states in the New England region and also include data from eight previously studied locations. Our data set emphasizes back azimuthal coverage necessary to capture the directional variation of splitting parameters expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 56 publications
(134 reference statements)
6
27
0
Order By: Relevance
“…These are endmember scenarios, and it is possible (perhaps likely) that the actual Earth structure incorporates elements of both ideas. On balance, we find the idea of a transition to upwelling flow in the upper mantle at the eastern end of the SEISConn array (Figure 13a) to be compelling, since Li et al (2019) has persuasively demonstrated that the region of weak splitting in eastern Connecticut is connected geographically with the region of weak splitting above the NAA first documented by Levin et al (2018). While a scenario in which pervasive N-S oriented anisotropy in the mantle lithosphere exhibits lateral variability in its strength, with weak lithospheric anisotropy in the west and strong lithospheric anisotropy in the east (Figure 13b), is also possible, we do not have a ready explanation for why such a variation in lithospheric anisotropy strength would be present.…”
Section: Possible Models For Upper Mantle Anisotropy Beneath Southernmentioning
confidence: 86%
See 4 more Smart Citations
“…These are endmember scenarios, and it is possible (perhaps likely) that the actual Earth structure incorporates elements of both ideas. On balance, we find the idea of a transition to upwelling flow in the upper mantle at the eastern end of the SEISConn array (Figure 13a) to be compelling, since Li et al (2019) has persuasively demonstrated that the region of weak splitting in eastern Connecticut is connected geographically with the region of weak splitting above the NAA first documented by Levin et al (2018). While a scenario in which pervasive N-S oriented anisotropy in the mantle lithosphere exhibits lateral variability in its strength, with weak lithospheric anisotropy in the west and strong lithospheric anisotropy in the east (Figure 13b), is also possible, we do not have a ready explanation for why such a variation in lithospheric anisotropy strength would be present.…”
Section: Possible Models For Upper Mantle Anisotropy Beneath Southernmentioning
confidence: 86%
“…While the long-running stations used by Li et al (2019) allowed for a much more detailed characterization of splitting behavior at each station, the comparatively short-lived SEISConn array offers the advantage of a much larger number of stations. The Li et al (2019) study included data from just one station in northern Connecticut (UCCT, located just to the south of SEISConn), while our dataset, with 15 stations, allows us to probe the anisotropic boundary proposed by Li et al (2019) in greater detail and at higher resolution. Figure 12 shows our single-station average splitting measurements (as derived from the multichannel method using the low-frequency filter) plotted on top of the anisotropic domains proposed by Li et al (2019).…”
Section: Sk(k)s Splitting At Terrane Boundaries and Regional Anisotromentioning
confidence: 99%
See 3 more Smart Citations